Cours particulier avec Paul B. Preciado (1/2) (2019)
« Féminin » ou « masculin » ? Dès la naissance, il faut choisir. Sur les papiers d’identité, les formulaires d’inscription, les bulletins d’adhésion, il y a toujours ces deux petites cases à cocher. Comme si le monde se divisait en deux catégories : les hommes et les femmes. C’est oublier que le genre est une fiction, un discours biopolitique. C’est oublier, aussi, que l’identité n’est jamais une essence mais une construction. D’où vient cette binarité du genre ? Pourquoi la citoyenneté n’est réservée qu’aux personnes cisgenres ? Comment déconstruire ce rapport normatif entre sexe, genre et reproduction ? Pour dépasser cette dichotomie de genre, Victoire Tuaillon reçoit Paul B. Preciado, philosophe, commissaire d’exposition et auteur dans un grand entretien en deux épisodes. La suite de ce cours particulier sera disponible dès le 9 mai 2019. RÉFÉRENCES CITÉES DANS L’ÉMISSION Retrouvez toutes les références et ressources de l'épisode à l'adresse https://www.binge.audio/podcast/les-c... CRÉDITS Les couilles sur la table est un podcast de Victoire Tuaillon produit par Binge Audio. Réalisation : Quentin Bresson. Stagiaire : Nadia Chapelle. Générique : Théo Boulenger. Identité graphique : Sébastien Brothier (Upian). Chargée de production : Juliette Livartowski. Chargée d’édition : Diane Jean. Direction des programmes : Joël Ronez. Direction de la rédaction : David Carzon. Direction générale : Gabrielle Boeri-Charles.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; philosophie; pol5480; premier cycle; ressource en ligne; sciences humaines; thématiques; transféminisme

Responses to structural violence: The everyday ways in which queer and trans migrants with precarious status respond to and resist the Canadian immigration regime - Edward Ou Jin Lee (International Journal of Child, Youth & Family Studies, 2019)
This article examines how the Canadian immigration regime socially organizes the everyday lives of queer and trans migrants with precarious status. Drawing from key findings from an institutional ethnographic study, this article maps out the disjuncture between the actual experiences of queer and trans migrants with precarious status and the ideological and textual production of precarious status by the Canadian state. Making explicit this disjuncture reveals how the Canadian immigration regime enacts structural violence upon queer and trans migrants. This article also engages with the response-based approach to violence in order to understand how queer and trans migrants actively respond to this violence. In doing so, this article highlights the ways in which queer and trans migrants respond and resist the structural violence integral to the Canadian state’s production of precarious status.
Disponible en ligne: http://dx.doi.org/10.18357/ijcyfs101201918807 Donné à lire au cours POL4212.
Keywords: LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; identités LGBTQIA2+; immigration; pol4212; premier cycle; queer; ressource en ligne; régions géographiques; thématiques; transféminisme; violences

Trans self-identification and the language of neoliberal selfhood: Agency, power, and the limits of monologic discourse - Zimman, Lal (International Journal of the Sociology of Language, 2019)
Sociocultural linguists share with transgender communities a strong interest in the power of individuals to assert agency over linguistic patterns. For trans people, a key principle of activism is gender self-determination, which treats each individual as the ultimate authority on their own gender identity. This article explores some of the ways gender self-determination and self-identification surface in transgender people’s linguistic practices. Three particular manifestations are highlighted: gendered identity labels, third person pronouns, and body part terminology. The observations offered on these subjects are based on a series of ethnographic projects carried out from 2006–2016 in transgender communities across several metropolitan areas in the United States and in online spaces frequented by trans people. However, the analysis goes beyond mere description by treating this kind of individualized linguistic agency as the product of cultural practice rather than an asocial given. Such a perspective introduces questions concerning why this form of agency arose in the time and place that it has. This article frames gender self-identification as an enactment of neoliberal personhood, in which individuals are framed as the driver of their destiny. What the ideology of neoliberal agency obscures, however, is that agency is not an equally distributed resource.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; agentivité; amériques; approches et analyses; cours; discipline; identités LGBTQIA2+; lin2685; linguistique; néolibéralisme; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sofia; thématiques; transféminisme; états-unis